2002
DOI: 10.1111/1540-4560.00248
|View full text |Cite
|
Sign up to set email alerts
|

Internet Paradox Revisited

Abstract: Kraut et al. (1998) reported negative effects of using the Internet on social involvement and psychological well‐being among new Internet users in 1995–96. We called the effects a “paradox” because participants used the Internet heavily for communication, which generally has positive effects. A 3‐year follow‐up of 208 of these respondents found that negative effects dissipated. We also report findings from a longitudinal survey in 1998–99 of 406 new computer and television purchasers. This sample generally exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

73
1,143
13
77

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,682 publications
(1,306 citation statements)
references
References 52 publications
73
1,143
13
77
Order By: Relevance
“…However, this hypothesis is not supported by evidence indicating that computer use can lead to improved social networks and communication [18]. Thus, it may be that it is the purpose of the behaviour or the motivation to engage in it that is key in determining the relationship with psychological health, rather than the duration of participation.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, this hypothesis is not supported by evidence indicating that computer use can lead to improved social networks and communication [18]. Thus, it may be that it is the purpose of the behaviour or the motivation to engage in it that is key in determining the relationship with psychological health, rather than the duration of participation.…”
Section: Resultsmentioning
confidence: 96%
“…GHQ-12, General Health Questionnaire. Model 1 adjusted for age (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), 40-54, 55+ years). Model 2 additionally adjusted for marital status (single, partner noncohabiting, partner cohabiting, separated/divorced, widowed), education (no qualifications, GCSE/other, A-level/degree), household income (unknown / prefer not to say,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is evidence suggesting that heavy use of the Internet may weaken social connections which in turn could lead to increased feelings of social isolation and depression. 36,37 These men may be seeking sexual partners and using club drugs to help alleviate these feelings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a longitudinal follow-up to the original HomeNet study found no long-term effects of Internet use on loneliness or depression (Kraut et al, 2002). Valkenburg, Peter, and Schouten (2006) note a major shortcoming of previous Internet research.…”
Section: Does Participation In Sns Affect Psychological Well-being Anmentioning
confidence: 99%